КАРБОНАТЫ ИЗ МЕТАСОМАТИТОВ И ЖИЛ ГУМЕШЕВСКОГО СКАРНОВОГО МЕДНО-ПОРФИРО - ВОГО МЕСТОРОЖДЕНИЯ (СРЕДНИЙ УРАЛ): СОСТАВ И ГЕОТЕРМОБАРОМЕТРИЯ - Грабежев А.И.; Мурзин В.В.; Сотников В.И.; Боровиков А.А.; Ронкин Ю.Л.; Гмыра В.Г.; Пальгуева Г.В. (My University, 2005)
The ore-bearing carbonate metasomatites of the retrograde stage are very widespread in the Early Devonian Gumeshevskoye deposit. Skarns and epidotites are replaced by epidote-actinolite-magnetite-calcite rocks (MgCO3 = 0.4-0.9, FeCo3 = 0.3-0.6 %mol, molar percent here and further). Marbles are usually replaced by the banded silicate (chlorite, talc, actinolite)-magnetite-quatz-calcite (MgCO3 = 0.4-2.6, FeCO3 = 0.5-1.6)-anke-rite (FeCO3 = 6-11) metasomatites. Talc-magnetite-calcite (MgCO3 = 0.3-1.4, FeCO3 = 0.1-0.2)-dolomite (FeCO3 =2-4) metasomatites were met also. Nearly everywhere, the metasomatites are replaced by chalcopyri-te-pyrite association, but there are also the later metasomatic calcite (MgCO3 = 0.1-1.5, FeCO3 = = 0.04-0.08)-sulfide aggregates in the marble. Veins and veinlets are formed by calcite (MgCO3 = 0.1-0.5, FeCO3 = 0.1-0.4), sometimes in association with dolomite (FeCO3 = 3-9). Isotope parameters of carbonate (δ
Keywords: 549.74:553.43(470.5)